The Mediating Role of Financial Self-Efficacy between Digital Financial Literacy and Financial Well-Being among Youth - Herma Wiharno; Yanneri Elfa Kiswara Rahmantya; Odang Supriatna (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The increasing use of digital financial services among youth has not been matched by adequate digital financial competencies, creating risks that may negatively affect their financial well-being. This study aims to analyze the effect of digital financial literacy on financial well-being and examine the mediating role of financial self-efficacy in this relationship. Using a quantitative approach, data were collected from 380 university students through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that digital financial literacy has a positive and significant effect on financial well-being, indicating that stronger digital financial capabilities enhance individuals’ ability to manage financial decisions in a digital environment. Financial self-efficacy also shows a significant positive influence on financial well-being and further strengthens the relationship between digital financial literacy and financial well-being. These findings highlight that psychological readiness plays an essential role in translating digital financial knowledge into effective financial behavior. The study contributes to the growing literature by integrating digital and psychological dimensions into a unified model of financial well-being. Practically, the results emphasize the need for targeted digital financial education and confidence-building initiatives to enhance financial resilience among youth in an increasingly digitalized economy. Keywords: Digital Financial Literacy; Self-Efficacy; Financial Well-Being; Youth; PLS-SEM